The Santa Clara County Reentry Resource Center: Reentry Service Linkage and the One-Stop Shop Model - Redlich, Rose (2018)
AB 109 has resulted in a significantly greater need for reentry programs and services across California. Many county law enforcement officials now view reentry programs and services as a promising approach for keeping recidivism rates low. Santa Clara County has recognized the value of well-coordinated, quick, and efficient reentry service delivery. In response to AB 109, the Office of the Sheriff and Department of Correction partnered with the Probation Department, Office of the County Executive, Behavioral Health Services Department, Custody Health Department, Ambulatory Care, and the Social Services Agency to establish the Santa Clara County Reentry Resource Center (SCCRC) in February 2012. Santa Clara County is one of only two counties in California (Los Angeles County is the other) to implement a one-stop shop model for reentry service delivery. It is also the only county in Northern California to offer such a large variety of rehabilitative services to its reentry population. The purpose of this study was to examine the SCCRC's one-stop shop model to determine if the model is fulfilling its goal of linking clients to reentry services